MEMPELAJARI SIFAT FISIKO-KIMIA DEKSTRIN SAGU BUATAN DAN KOMERSIAL - Bambang Wiyono; Toga Silitonga (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
Sago starch contains about 84. 7% carbohydrate. Further analysis of the carbohydrate indicate that about 73% consist of amylopectin (the branched polymers) and 27% amylase (the linear polymers). These components are potentially contributing to the production of sago-dextrin. The purpose of this research is to analyse the physico-chemical properties of the laboratory made sago-dextrin and the properties of the commercial one, to compare with the Indonesian Industrial Standard requirements for dextrin. The results indicated that the ash content and acidity, of both the experimental and the commercial sago dextrins have met the Indonesian Industrial Standard. The solubility in cold water, dextrose content of the commercial dextrin, and the moisture content of the experimental one have not met the Indonesian Industrial Standard. Higher yield can be obtained by using acid concentration below 0.05 M as catalyst and or hydrolyzing time under 5 minutes during the dextrin making process.